Relational Comparison and LGBTQ Activism in European Cities. (17th February 2014) - Binnie, Jon
Abstract This article examines the role of city twinning as a device for conducting transnational activism around lesbian, gay, bisexual, transgender and queer (LGBTQ) politics. It focuses on the city of Leiden in the Netherlands, examining how the city's twinning links with the cities of Torun in Poland and Oxford in the UK have been used at different times as a device to mobilize transnational solidarities with LGBTQ people outside of the Netherlands. Drawing on qualitative semi‐structured interviews with LGBTQ activists in Leiden as part of a wider study of transnational LGBTQ activism in Europe, I seek to understand how twinning links are used to forge sustainable solidarities both across national boundaries and within Leiden. I suggest that relational comparisons about the status and treatment of sexual dissidents in Leiden and its twin cities are central to the production of these solidarities. While twinning has significant potential as a device for the production of sustainable transnational LGBTQ activism, I also suggest that it can be used to advance problematic geo‐temporalities about the relative 'progressiveness' or 'backwardness' of LGBTQ politics in specific cities.